THE EFFECT OF ONLINE CUSTOMER REVIEW AND ONLINE CUSTOMER RATING ON PURCHASE DECISIONS AT COPYRIGHT GRAFIKA STORE - Siti Nurhabibah; Citra Savitri; Syifa Pramudita Faddila (SEAN Institute, 2022)
The increasingly rapid technology in this modern era causes a shift in human behavior, especially in terms of shopping. If in the past when we wanted to shop, we had to come directly to the store we were looking for, now we no longer need to leave the house, just with a smartphone and an internet connection, we can already order the items we need. In purchasing decisions, consumers also need to pay attention to factors such as online customer reviews and online customer ratings. The research method uses quantitative, where the sampling technique used is the Slovin formula with the total population in this study as many as 139 Cipta Graphic shop customers so that the percentage of allowances is 5% and the calculation results can be rounded up to achieve conformity, then the sample taken is 103 respondents and then analyzed by multiple linear regression, t test, F test and the coefficient of the determinant. all data is processed using IBM SPSS 26. The results of this study (1) online customer review significantly influences purchasing decisions at the Cipta Graphic store. (2) online customer rating significantly influences purchasing decisions at Cipta Graphic stores, (3) online customer reviews and online customer ratings simultaneously and significantly influences purchasing decisions at Cipta Graphic stores.